DAMPAK PERTAMBAHAN PENDUDUK TERHADAP KONVERSI LAHAN KECAMATAN LUBUK ALUNG KABUPATEN PADANG PARIAMAN TAHUN 2005-2020 - zalni, fina okta; Suasti, Yurni (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This study aims to (1) determine the population growth in Lubuk Alung District during the 2005-2020 period of 5 years. (2) identify Land Conversion in Lubuk Alung District during 2005-2020. (3) determine the impact of population growth on land conversion in Lubuk Alung District. The method used in this study is quantitative method. The population of this study was the population of Lubuk Alung District, Padang Pariaman Regency and residential land use in 2005-2010, 2010-2015, 2015-2020. The data was analyzed by Calculating population growth and the statistical test used was Pearson's Moment Product correlation statistical analysis. The results showed that there was a population increase in 2005-2020 within a period of 15 years, in 2005-2010 with a population increase of 1.56%, in 2010-2015 there was a decrease in population by 0.78%, in 2015-2020 it increased again by 0.93%. There is an increase in land conversion due to the increasing number of population growth in Lubuk Alung District in 2005 – 2020 within a period of five periods with a span of 15 years